Representações sobre o patrimônio: participação popular nas políticas habitacionais de interesse social no Centro Histórico de São Luís – MA - SILVA, Ivanilde da Conceição (2019)
Public housing policies in Brazil have been following a linear trend since the 1930s, when the state began to admit that housing issues were directly linked to the social, economic and political order. In this sense, the State began to intervene by adopting measures that reduce the housing deficit and provide residents, especially in urban areas, with housing with adequate infrastructure. In Brazil's public housing policies are inserted policies that were developed specifically to reduce housing deficit of the historical centers of the safeguarded cities, taking into account the fact that they are considered Brazilian cultural heritage. Moreover, this research objective is to understand how the participation of the historical center residents regarding housing public policies related to the social interest over the historical center of São Luís occurs. For this purpose, research is framed as a case study: it has a qualitative approach supported by bibliographical surveys and uses observation in loco and semi-structured interviews as instruments of data collection. In order to achieve the objectives above mentioned, it is necessary to undertake an analysis on how does a world cultural heritage city is constituted and how do the housing policies focused on historical centers are developed, emphasizing the Historical Center of São Luís. After these studies, it was possible to verify that, despite the efforts of the organs responsible for the protection of these patrimonial spaces in the development of partnerships with other national and international bodies in order to formulate specific policies to revitalize the central areas and to alleviate housing deficits, has not yet been sufficient to meet the demands of the population.